X-linked sideroblastic anaemia in a female fetus: a case report and a literature review - Diane Nzelu; Panicos Shangaris; Lisa Story; Frances Smith; Chinthika Piyasena; Jayanthi Alamelu; Amira Elmakky; Maria Pelidis; Rachel Mayhew; Srividhya Sankaran (BMC, 2021)
Abstract Background X-linked sideroblastic anaemia (XLSA) is commonly due to mutations in the ALAS2 gene and predominantly affects hemizygous males. Heterozygous female carriers of the ALAS2 gene mutation are often asymptomatic or only mildly anaemic. XLSA is usually characterized by microcytic erythrocytes (reduced mean corpuscular volume (MCV)) and hypochromia, along with increased red cell distribution width. However, in females with XLSA the characteristic laboratory findings can be dimorphic and present with macrocytic (elevated MCV) in addition to microcytic red cells. Case presentation We report a case of fetal anaemia, presenting in the early third trimester of pregnancy, in a female fetus. Ultrasound findings at 29 weeks were of cardiomegaly, prominent umbilical veins, a small rim of ascites, and mean cerebral artery peak systolic velocity (PSV) value above 1.5 Multiples of the Median (MoM). She underwent non-invasive prenatal testing that determined the rhesus genotype of the fetus to be rhesus B negative. No red blood cell antibodies were reported. Other investigations to determine the underlying cause of fetal anaemia included microarray comparative genomic hybridization, serology to exclude congenital infection and a peripheral blood film and fetal bilirubin to detect haemolysis. The maternal grandmother had a history of sideroblastic anaemia diagnosed at the age of 17 years. The mother had mild macrocytic anaemia with haemoglobin of 10.4 g/dl and MCV of 104 fl. The fetal anaemia was successfully treated with two in utero transfusions (IUTs), and delivery occurred via caesarean section at 37 weeks of gestation. The red cell gene sequencing in both the mother and fetus were heterozygous for an ALAS2 mutation causing in utero manifestations of XLSA. The haemoglobin on discharge to the local hospital at five days of age was 19.1 g/dl. Subsequently, the infant became anaemic, requiring regular 3-4 monthly blood transfusions and demonstrating overall normal development. Her anaemia was unresponsive to pyridoxine. Conclusions This is one of four cases reporting multiple female members presenting with discordant clinical features of XLSA from being entirely asymptomatic to hydropic in utero. Our report is novel in that there are no previous cases in the literature of anaemia in a female fetus heterozygous for ALAS2 mutation.